2014
DOI: 10.1038/bjc.2014.423
|View full text |Cite
|
Sign up to set email alerts
|

HLA and KIR genotyping correlates with relapse after T-cell-replete haploidentical transplantation in chronic myeloid leukaemia patients

Abstract: Background:Conflicting results have been reported regarding the predicative roles of alloreactive natural killer (NK) cells on the outcomes of transplantation in leukaemia patients.Methods:We prospectively analysed the human leukocyte antigen (HLA) typing of donor–recipient pairs and the KIR typing of the donors in 97 CML patients to address the predictive roles of NK cells in relapse undergoing T-cell-replete haploidentical transplantation.Results:Patients with class I ligands for the donor-inhibitory KIR gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…There was an increase in the functional recovery of donor‐derived NK cells in recipient presenting ligands for donor inhibitory KIRs, which correlated with better relapse control. These findings are in agreement with previous findings, where a high relapse rate following transplantation was associated with missing self or missing ligands in the recipients . These findings suggest that recipients with a full complement of KIR ligands for donor KIR inhibitory receptors promote the NK‐cell licensing, and therefore provide the greatest protection against relapse in T‐cell‐replete haploidentical transplants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was an increase in the functional recovery of donor‐derived NK cells in recipient presenting ligands for donor inhibitory KIRs, which correlated with better relapse control. These findings are in agreement with previous findings, where a high relapse rate following transplantation was associated with missing self or missing ligands in the recipients . These findings suggest that recipients with a full complement of KIR ligands for donor KIR inhibitory receptors promote the NK‐cell licensing, and therefore provide the greatest protection against relapse in T‐cell‐replete haploidentical transplants.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, we successfully established a novel haploidentical stem cell transplantation (haplo‐SCT) protocol that includes antithymocyte globulin treatment followed by unmanipulated blood and marrow graft infusion without in vitro T‐cell depletion . As described in our original report of T‐cell‐replete haplo‐SCT, we observed that patients lacking class I ligands for donor KIR ligand or donor‐inhibitory or donor‐activating KIR gene had higher relapse rate—a result that directly contradicts the findings of the Perugia group . The results suggests that the presence of class I ligands for the donor‐activating or donor‐inhibitory KIR gene in the recipient might confer some protection against leukemic relapse in T‐cell‐replete haplo‐SCT.…”
Section: Introductionmentioning
confidence: 84%
“…Our previous studies demonstrated that NK cell licensing is promoted in unmanipulated haploidentical SCT (haplo-SCT) recipients presenting class I ligands for donor inhibitory KIRs, leading to a decreased relapse rate Zhao et al, 2007Zhao et al, , 2014Zhao et al, , 2015. Further, Sekine et al (2016) demonstrated that cord blood (CB) selection based on the combination of NK cell licensing and activation of KIRs may improve patient outcome after CB transplantation (CBT).…”
Section: Discussionmentioning
confidence: 99%
“…Our previously published data have demonstrated that recipient expression of ligands for donor inhibitory KIRs enhances NK cell function to control leukaemic relapse after haploidentical transplantation (Zhao et al, 2014(Zhao et al, , 2015. On this basis, we further demonstrated that CMV reactivation was reduced when donor KIRs were ligated by recipient and donor class I at the same time, when compared with donorhost partnerships in which donor KIRs were ligated by donor but not recipient class I or were ligated by recipient but not donor class I or KIRs that were ligated by neither donor nor recipient class I.…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation of T-replete marrow or blood cell grafts obtained from haploidentical donors, using modified immune-suppressive conditioning regimen such as those including posttransplant cyclophosphamide, represent a more widely applicable procedure, in which to further explore the potential contribution of alloreactive NK cells in posttransplant clinical events. Unexpectedly, a recently published report suggests that, in this context, the presence of recipient class I ligands to donor KIR receptors confers some protection to the recipient against leukemia relapse, an observation that needs further confirmation and would imply a role for killer activating receptors (KAR) as much as for KIR (20). The role of alloreactive NK cells remains more elusive in the context of HSCT performed from other categories of donors.…”
Section: Medical Applications Of Nk Cell Manufacturing and Adoptive Tmentioning
confidence: 99%